PENGARUH KEBIJAKAN DIVIDEN, CORPORATE GOVERNANCE, FREE CASH FLOW, DAN PERTUMBUHAN PENJUALAN TERHADAP MANAJEMEN LABA - Turot, Margaretha (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This study aims to analyze the effect of dividend policy, corporate governance, This study aims to analyze the effects of dividend policy, corporate governance, free cash flow, and sales growth on earnings management. The method used is quantitative method. The sample determination method uses a purposive sampling method with samples used in manufacturing companies listed on the Indonesia Stock Exchange (IDX) respectively in 2010-2015 to view the published financial statements. The results showed that the effect of dividend policy, management ownership, ownership of domestic institutions, ownership of foreign institutions, public ownership partially had no effect on earnings management while free cash flow, and sales growth partially affected earnings management.